Pelarangan Tiktok Shop dalam Perspektif Keadilan Ditinjau dari Sosiological Jurisprudence - Abdurrahman, Irfan (Bayani, 2025)
In fact, the regulation regarding the prohibition of TikTok Shop from operating in Indonesia as stated in the Regulation of the Ministry of Trade of the Republic of Indonesia Number 31 is more binding on the owners or managers of the application. However, TikTok traders, in this case, people who do business using TikTok media, certainly feel very disadvantaged regarding the regulation that prohibits them from continuing the business they have pioneered so far. Of course, this is an issue of injustice in society caused by the issuance of statutory regulatory products. So through research in this journal, the author attempts to analyze the Prohibition of TikTok Shop from the Perspective of Justice Reviewed from Sociological Jurisprudence. This study uses a normative legal research method with a conceptual and statutory approach. The discussion that has been carried out on the study that discusses the prohibition of TikTok Shop from the perspective of justice reviewed using the sociological jurisprudence understanding. Where we understand that justice is not necessarily seen from one side only, because justice cannot satisfy and provide benefits to one party. While this decision has harmed many parties, we cannot close our eyes to the fact that this policy has also saved many other parties.